PENGGUNAAN SUPERVISI ARTISTIK DALAM MANAJEMEN PENDIDIKAN ISLAM - Wahyono, Imam; Gojali, Imam (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The success of Islamic education is a joint effort of Islamic educational institutions, government and society. One of the supporting factors for the achievement of educational goals is good management of educational institutions. Supervision is one of the functions of education management. Artistic supervision as a form of supervision of educational institutions functions to provide assistance to teachers in the form of direction and guidance for improving the learning process. The implementation of artistic supervision needs to be maximized in Islamic educational institutions, so that it is not incidental. The purpose of this study is to analyze artistic supervision in Islamic education management. The research method used is literature study. Data were collected through documentation which was then analyzed descriptively. The results of the research found that the actualization stages of artistic supervision in Islamic education management include planning, implementing, and evaluating based on Islamic values that are sourced from the Al Quran and Hadith; supervision is a collaboration of the principal, supervisors, expert supervisors, and external supervisors. Supervision can be carried out individually or in groups.